2013
DOI: 10.1007/s00535-012-0738-1
|View full text |Cite
|
Sign up to set email alerts
|

Dental infection of Porphyromonas gingivalis exacerbates high fat diet-induced steatohepatitis in mice

Abstract: Dental infection of P.g. may play an important role in NASH progression through upregulation of the P.g.-LPS-TLR2 pathway and activation of inflammasomes. Therefore, preventing and/or eliminating P.g. infection by dental therapy may have a beneficial impact on management of NASH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
162
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(170 citation statements)
references
References 41 publications
4
162
0
4
Order By: Relevance
“…Recently, it was reported that P.g. was detected in the livers of patients with non-alcoholic fatty liver disease (NAFLD), including non-alcholic fatty liver and nonalcholic steatohepatitis (NASH) [15,28]. In NAFLD, excessive delivery of free fatty acids and imbalance in lipid synthesis cause increased fat accumulation in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that P.g. was detected in the livers of patients with non-alcoholic fatty liver disease (NAFLD), including non-alcholic fatty liver and nonalcholic steatohepatitis (NASH) [15,28]. In NAFLD, excessive delivery of free fatty acids and imbalance in lipid synthesis cause increased fat accumulation in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Previous animal experiments showed that intravenous injection (Yoneda et al, 2012) and direct application via dental pulp (Furusho et al, 2013) of P. gingivalis exacerbated steatohepatitis in murine models fed HFD. However, the results in these experiments were not related to periodontitis induced by P. gingivalis infection.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Furusho et al reported that when P. gingivalis was administered into the pulp chamber in steatosis model mice fed HFD, hepatic lipid deposition and focal fibrosis developed in mice with periapical lesions, as compared to control animals without P. gingivalis infection (Furusho et al, 2013). These observations largely agree with our results using experimental periodontitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The normal gut microbiota carries out specific functions in host nutrient metabolism, xenobiotic and drug metabolism, structural integrity maintenance of the gut mucosal barrier, immunomodulation, and protection against pathogens 11, 12, 13, 14, 15. Recently, the gut microbiome has been shown to play a crucial role in health, as well as in diseases such as obesity,16 inflammatory bowel disease,17, 18 diabetes,19, 20 non‐alcoholic fatty liver disease,21, 22, 23 and several types of cancers 24, 25. Experimental evidence indicates that the human intestinal microbiome can influence tumor development and progression in the gastrointestinal tract by damaging DNA, activating oncogenic signaling pathways, producing tumor‐promoting metabolites, and suppressing the antitumor immune response 7, 25, 26, 27, 28, 29.…”
Section: Introductionmentioning
confidence: 99%